Black carbon yields highest nutrient and lowest arsenic release when using rice residuals in paddy soils. Issue 1 (December 2018) - Schaller, Jörg; Wang, Jiajia; Islam, Md.; Planer-Friedrich, Britta
Abstract Rice straw increasingly remains on the fields for nutrient supply to the next generation of crop plants. It can be applied either fresh or after burning to black carbon or ash. A central concern during rice cultivation is accumulation of carcinogenic arsenic and the question arises how much rice straw application contributes to nutrient versus arsenic supply in paddy fields. Laboratory incubation experiments were performed to assess the effect of rice straw, black carbon and ash on element mobilization. Our experiments showed initially higher silicon and phosphorus release from black carbon compared to fresh straw amendments. However, more re-sorption to soil lead to finally slightly lower pore water concentrations for black carbon versus fresh straw amendments. Highest arsenic, iron, manganese and dissolved organic carbon concentrations were observed after fresh rice straw application. Black carbon and ash application lead to only minor increases of arsenic compared to controls without amendments. Overall, for silicon and phosphorus the soil acts as sink while for iron and arsenic it was the main source. In summary, burning of rice straw to black carbon prior to application seems to yield a high increase in desired nutrient and a decrease in undesired arsenic mobilization in paddy soils.